Association between ErbB4 single nucleotide polymorphisms and susceptibility to schizophrenia: A meta-analysis of case-control studies. Issue 8 (February 2017) - Feng, Yanguo; Cheng, Dejun; Zhang, Chaofeng; Li, Yuchun; Zhang, Zhiying; Wang, Juan; Feng, Xiao
Abstract: Background: Accumulating studies have reported inconsistent association between ErbB4 single nucleotide polymorphisms (SNPs) and predisposition to schizophrenia. To better interpret this issue, here we conducted a meta-analysis using published case-control studies. Methods: We conducted a systematic search of MEDLINE (Pubmed), Embase (Ovid), Web of Science (Thomson-Reuters) to identify relevant references. The association between ErbB4 SNPs and schizophrenia was assessed by odds ratios (ORs) and 95% confidence intervals (CIs). Between-study heterogeneity was evaluated by I squared ( I 2 ) statistics and Cochran's Q test. To appraise the stability of results, we employed sensitivity analysis by omitting 1 single study each time. To assess the potential publication bias, we conducted trim and fill analysis. Results: Seven studies published in English comprising 3162 cases and 4264 controls were included in this meta-analysis. Meta-analyses showed that rs707284 is statistically significantly associated with schizophrenia susceptibility among Asian and Caucasian populations under the allelic model (OR = 0.91, 95% CI: 0.83–0.99, P = 0.035). Additionally, a marginal association ( P < 0.1) was observed between rs707284 and schizophrenia risk among Asian and Caucasian populations under the recessive (OR = 0.85, 95% CI: 0.72–1.01, P = 0.065) and homozygous (OR = 0.84, 95% CI: 0.68–1.03, P = 0.094) models. In the Asian subgroup, rs707284 was also noted to be marginally associated with schizophrenia under the recessive model (OR = 0.84, 95% CI: 0.70–1.00, P = 0.053). However, no statistically significant association was found between rs839523, rs7598440, rs3748962, and rs2371276 and schizophrenia risk. Conclusion: This meta-analysis suggested that rs707284 may be a potential ErbB4 SNP associated with susceptibility to schizophrenia. Nevertheless, due to the limited sample size in this meta-analysis, more large-scale association studies are still needed to confirm the results. Abstract : Supplemental Digital Content is available in the text